Penerapan Metode Least Significant Bit Dalam Perlindungan Hak Cipta Pada Kain Cepuk - Prananda, Made Yayang; Kadyanan, I Gusti Agung Gede Arya; Putra, I Gusti Ngurah Anom Cahyadi; Suhartana, I Ketut Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2024)
Cepuk cloth is one of the typical crafts of Tanglad Village, Nusa Penida District, Klungkung Regency, Bali, which comes from ancestors and is passed down from generation to generation. Cepuk cloth also supports tourist attractions in Nusa Penida which need development and preservation such as digitalization. However, digitalization will add new problems in terms of ownership. Therefore, the author wants to conduct research that is used to build a website-based application by inserting valid proof of ownership using a digital signature, namely a Quick Response (QR) code. Proof of ownership will be encrypted using the Advanced Encryption Standard (AES) cryptographic algorithm before being used as a digital signature. Meanwhile, the insertion method uses the LSB method. The research carried out was successful based on the results of computational testing in tests without attacks showing imperceptibility, there was no difference between the stego image and the original image, then fidelity obtained an average MSE value of 0.5 and PSNR 51 dB, the recovery results stated that the inserted embedded image was successfully extracted , and tests with attacks on robustness by manipulating or editing truncation , changing resolution and inversion have unextractable results. Meanwhile, the rotation of the stego image can be maintained and produces plaintext when extracted. Another measure of success is based on software testing using black box testing to find that the functional application works well and there are no problematic features.